Community health nurses' concerns about infant regulatory problems are predictive of mental disorders diagnosed at hospital: a prospective cohort study - Pant, Sofie Weber; Holstein, Bjørn Evald; Ammitzbøll, Janni; Skovgaard, Anne Mette; Pedersen, Trine Pagh (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction Regulatory problems of eating, sleeping, and crying in infancy may index mental health vulnerability in older ages, and knowledge is needed to inform strategies to break the developmental trajectories of dysregulation in early childhood. In this study, we examined the prospective associations between infant regulatory problems at the age of 8–10 months identified by community health nurses (CHN) and mental disorders diagnosed in hospital settings in children aged 1–8 years. Methods From a cohort of all newborn children in 15 municipalities in the Capital Region of Copenhagen (N = 43,922) we included all children who were examined by CHNs at the scheduled home visit at the age of 8–10 months (N = 36,338). Outcome measures were ICD-10 mental disorders diagnosed at public hospitals and reported to the National Patient Register. Logistic regression included data on child and family covariables obtained from population registers. Results The CHNs reported concerns regarding sleep in 7.7% of the study population, feeding and eating in 19.1%, combined sleeping and eating problems in 3.6%, and incessant crying in 0.7%. A total of 1,439 children (4% of the study population) were diagnosed in hospital settings with an ICD-10 mental disorder between the ages of 11 months and 8 years. Analyses adjusted for a range of perinatal and family adversities showed an increased risk of any neurodevelopmental disorder among children with CHN concerns of feeding and eating (odds ratio (OR) 1.36 (95% confidence interval (CI) 1.14–1.63)) and co-occurrent problems of feeding and eating and sleep (OR 1.60 (95% CI 1.14–2.26)). For autism-spectrum disorders, an increased risk was seen among children with co-occurrent problems of both feeding and eating and sleep (OR 1.73 (95% CI 1.07–2.79)). Concern about feeding and eating was also associated with an increased risk of behavioral and emotional disorders (OR 1.27 (95% CI 1.03–1.56)). Concern about incessant crying at the age of 8–10 months was not associated with a diagnosed mental disorder, but findings may reflect low statistical power due to low frequency of concern. Discussion CHN concerns mirror a group of developmentally vulnerable children. Further research is needed to explore the possibilities of preventive intervention within the general child health surveillance to address the developmental psychopathology of dysregulation in early ages.